Efecto de mallas protésicas intraperitoneales sobre suturas digestivas: Estudio controlado, pareado, randomizado - Gateño, Nisso (Cirugía del Uruguay, 1991)
A randomized, paired, controlled, prospectiva study was made. 48 rats used as /aboratory animals were operated on and divided into two groups: a control one in which only digestive suture and apposition to peritoneum was made, and a study group in which the suture was apposed to a prosthesic po/ypropylene mesh and a polyglactin 910 one. Resu/ts showed that there was no significant difference in peritonitis incidence due to suture fai/ure between both groups. Adherence formation and their firmess was a/so studied; adherences to the mar/ex mesh were significantly firmer and fibrosis was histologically more intense than in the case of the polyglactin 910 one.